From Student Activism to a Way of Life: The Student Activists-Turned-Peasant Activists in South Korea - Sik Son (Adult Education Research Conference, 2006)
this paper explores the life-experience of six student activists who turned themselves into peasants in their search for social justice and egalitarian society in South Korea. The praxis of the activists crossing class line in the social movement reveals their transformative learning process as well as the development of their own pedagogy of the oppressed.
Keywords: Social movement; education for social change; transformative learning